Political Activity of women and Men - the Psychosocial Determinants of Conventional Political Activity - Miluska, Jolanta; Kuświk, Justyna; Pająk-Patkowska, Beata (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2018)
Political activity is a type of social activity displayed by citizens. Observations and research indicate that gender can be a factor which conditions its degree and forms. Apart from biological gender, which shapes the societal roles of women and men, additional factors that are supposedly responsible for their activities include elements of the system of beliefs (i.e. acknowledged political values, conviction that political activity has an importance, level of satisfaction with democracy as well as individualism and collectivism understood as an element of individual’s mentality). The impact of those factors on degree of conventional political activities among women and men is the subject of surveys which were conducted in 2004, 2010, and 2014 on a group of 1048 students from Polish universities. The received results show that differences in political activity between surveyed men and women as well as varying determinants in both groups are slowly fading away. The most important predictors of women’s political activity include: conviction of its significance in democracy and (dis)satisfaction with the way it functions.

Aktywność polityczna jest jednym z rodzajów aktywności społecznej człowieka. Obserwacje i badania wskazują na znaczenie płci jako czynnika decydującego o jej poziomie i formach. Poza płcią biologiczną kształtującą role społeczne kobiet i mężczyzn, dodatkowymi czynnikami potencjalnie odpowiedzialnymi za ich aktywność, są elementy systemu przekonań, czyli uznawane wartości polityczne, przekonanie o wartości aktywności politycznej, poziom zadowolenia z demokracji oraz indywidualizm i kolektywizm traktowany jako element mentalności jednostki. Wpływ tych czynników na poziom kon-wencjonalnej aktywności politycznej kobiet i mężczyzn jest przedmiotem badań kwestionariuszowych przeprowadzonych w roku 2004, 2010 i 2014 na grupie 1048 studentów polskich uczelni. Uzyskane wyniki wskazują na powolne zanikanie różnic w poziomie aktywności politycznej badanych kobiet i mężczyzn oraz zróżnicowane jej uwarunkowania w obu grupach i w zależności od formy aktywności. Najważniejszymi predyktorami aktywności politycznej kobiet są: przekonanie o wadze aktywności w demokracji oraz (nie)zadowolenie z jej funkcjonowania.
Aktywność polityczna kobiet i mężczyzn - psychospołeczne uwarunkowania konwencjonalnej działalności politycznej
Keywords: political activity; gender; women’s political activity; youth; social role theory; aktywność polityczna; płeć; działalność polityczna kobiet; młodzież; teoria roli społecznej